Control, synchronisation and antisynchronisation of chaos in two non-identical Josephson junction models via sliding mode control and its FPGA implementation - Ramakrishnan, Balamurali; Tamba, Victor Kamdoum; Metsebo, Jules; Tokoue Ngatcha, DiaNorré; Rajagopal, Karthikeyan (Pramāṇa, 2023)
The control, synchronisation and antisynchronisation of chaos in Josephson junction (JJ) and linear piecewise JJ models via sliding mode control method are investigated in this paper. Thanks to the Routh–Hurwitz stability criterion, the sliding mode controllers are designed to control chaos in JJ models and achieve synchronisation schemes between two non-identical JJ models. Numerical simulations are shown to clarify and confirm the chaos control and synchronisation schemes. Finally, field programmable gate array (FPGA) implementation is designed to reproduce the above-mentioned results and its correctness is confirmed using the FPGA analysis.